Pengaruh Penggunaan AI terhadap Peningkatan Kompetensi Guru PAI dalam Pembelajaran Berbasis Digital - Zulfa, Novita Indana; Sulistyowati, Endang (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
This study examines the pedagogical and professional competencies of Islamic Religious Education (PAI) teachers in the digital learning era. Although artificial intelligence (AI) can support the learning process, many teachers have not utilized it optimally due to limited digital literacy and a lack of training. This study aimed to evaluate the impact of AI use on the competencies of Islamic Religious Education (PAI) teachers. The method used was quantitative with a descriptive correlational approach, involving 50 Islamic Religious Education (PAI) teachers in Yogyakarta selected by purposive sampling. Data were collected through questionnaires and analyzed using the Kolmogorov-Smirnov normality test, Pearson correlation, and simple linear regression using SPSS. The results showed that the use of AI significantly affected the competencies of Islamic Religious Education (PAI) teachers, with a p-value of 0.014 and r-value of 0.347, and a contribution of 12%. This finding highlights the importance of training and policies supporting AI integration in education. Continuous support in training and proactive education policies are essential to maximize the use of AI.